Comparaison entre une fabrication fromagère à pâte molle « Camembert » de type traditionnel et de type stabilisé - FERRAOUN, Mounia (My University, 2020)
Milk is a very perishable product and must therefore undergo many treatments in order to extend its shelf life, cheese is one of the most common forms of preserving it, its study of which is the fundamental point of our work and more particularly the "camembert" which is a cheese made from raw cow's milk, with a soft, slightly salted paste, with a bloomy rind, and with an undivided curd in the shape of a flat cylinder The aim of this work is the comparison between a soft cheese production "Camembert" of the traditional type and of the stabilized type by varying the use of lactic ferments and this by testing the mesophilic and thermophilic ferments also to make a physico-chemical control. raw material "raw cow's milk" and a physico-chemical, microbiological, organoleptic and rheological quality control of our finished product. Cheese of good hygienic quality must meet certain numbers of criteria, particularly in terms of standards and microbiology. These can only be obtained by applying good hygienic practices and good manufacturing practices at all stages of the product's life. The sensory characteristics of a cheese are determined by the composition of the milk (high in protein and fat) and the ferments used. The use of pure ferments in the manufacture of a stabilized soft paste type cheese has allowed obtaining a better cheese yield with an optimized ripening time and physicochemical, microbiological and sensory qualities of the finished product comparatively. with cheese made from an industrial ferment The use of "B" and "C" ferments resulted in a soft, smooth and slightly acidic Camembert. This product obtained the best classification during tasting tests. The latter is of better quality compared to the traditional standard product which ferments with the "A" ferment.
Keywords: Camembert; Comparison/traditional; stabilized type; mesospheric and thermophilic ferments; raw milk; a soft cheese